An effective approach of vapour assisted morphological tailoring for reducing metal defect sites in lead-free, (CH3NH3)3Bi2I9 bismuth-based perovskite solar cells for improved performance and long-term stability. (July 2018) - Jain, Sagar M.; Phuyal, Dibya; Davies, Matthew L.; Li, Meng; Philippe, Bertrand; De Castro, Catherine; Qiu, Zhen; Kim, Jinhyun; Watson, Trystan; Tsoi, Wing Chung; Karis, Olof; Rensmo, Håkan; et al.
Abstract: We present a controlled, stepwise formation of methylammonium bismuth iodide (CH3 NH3 )3 Bi2 I9 perovskite films prepared via the vapour assisted solution process (VASP) by exposing BiI3 films to CH3 NH3 I (MAI) vapours for different reaction times, (CH3 NH3 )3 Bi2 I9 semiconductor films with tunable optoelectronic properties are obtained. Solar cells prepared on mesoporous TiO2 substrates yielded hysteresis-free efficiencies upto 3.17% with good reproducibility. The good performance is attributed mainly to the homogeneous surface coverage, improved stoichiometry, reduced metallic content in the bulk, and desired optoelectronic properties of the absorbing material. In addition, solar cells prepared using pure BiI3 films without MAI exposure achieved a power conversion efficiency of 0.34%. The non-encapsulated (CH3 NH3 )3 Bi2 I9 devices were found to be stable for as long as 60 days with only 0.1% drop in efficiency. This controlled formation of (CH3 NH3 )3 Bi2 I9 perovskite films highlights the benefit of the VASP technique to optimize material stoichiometry, morphology, solar cell performance, and long-term durability. Graphical abstract: We have used vapour assisted solution process technique to prepare lead-free, non-toxic bismuth-based perovskite solar cells using BiI3 and BiI3 on reaction with CH3 NH3 I vapours (MAI(v) ) for different reaction times. By this stoichiometric tailoring and fine-tuning bismuth-based perovskite have shown record breaking performance with 3.17% hysteresis free efficiency (world record so far for CH3 NH3 BiI3 based perovskite solar cells) that retains for more than 60 days (>1440 h) under continuous 1 sun (Am1.5 G) illumination showing a breakthrough in the long-term stability. The figure represents BiI3 and multicolour absorber layers formed on reaction of BiI3 with MAI(v) for different reaction time and utilized in making solar devices.fx1 Highlights: For the first time a two-step vapour assisted solution process (VASP) technique was used to systematically react films of BiI3 with MAI vapours to form perovskite at different reaction time. On detailed investigation the stepwise formation mechanism of (CH3 NH3 )3 Bi2 I9 and the effect of metallic content on performance of solar cells was revealed. World record hysteresis-free, power conversion efficiency of 3.17% obtained for (CH3 NH3 )3 Bi2 I9 solar cells. The devices shown breakthrough in long-term stability, proving stable performance for more than 1440 h on continuous 1 sun illumination.